Assessing balance via cross-line laser in individuals with chronic ankle instability - Swails, Madison; Hardy, Emma; Dury, Jeanne; Thomas, Abbey C.; Linens, Shelley W.; Donovan, Luke (Frontiers in Sports and Active Living, 2025)
IntroductionChronic ankle instability (CAI) is a condition characterized by recurring lateral ankle sprains and bouts of instability. Individuals with CAI have poor balance, a factor in the development, progression, and recovery of the condition. Individuals with improved balance report fewer CAI-related symptoms. Thus, accurate balance assessment is crucial to recovery from CAI. The gold standard for measuring balance is using force plates. Although sensitive to subtle changes in balance, the force plate's clinical utility is diminished due to high associated costs. Alternatively, a low-cost cross-line laser may serve as a surrogate to the gold standard within a clinical setting. Therefore, the purpose of this study was to validate the cross-line laser as a tool for balance assessment in comparison with the gold-standard force plate.MethodsTwenty-four individuals with CAI in a single-limb stance balanced on a force plate for three 10 s trials in eyes-open and eyes-closed conditions with a cross-line laser strapped to the top of their foot. A camera in front of the force plate captured the movement of the cross-line laser. Utilizing a tracking software, a virtual marker was placed on the cross-line laser that quantified the movement of the cross-line laser.ResultsThe results of this study found that cross-line laser outcomes, such as speed, horizontal velocity, total distance, and resultant velocity measures, had moderate-to-strong relationships to force plate outcomes, such as center of pressure (CoP) average velocity, and CoP 95% area (r = 0.46–0.87) and CAI patient-reported symptoms (r = 0.44–0.52) indicating that these measures could be used twofold.ConclusionThis study validates the cross-line laser as a balance assessment tool that may serve as a low-cost instrument to quantify balance.